A Case Report of Paradoxical Air Embolism Caused by Intrapulmonary Shunting During Liver Transplantation. Issue 3 (March 2017) - Badenoch, Adam; Srinivas, Coimbatore; Al-Adra, David; Selzner, Markus; Wąsowicz, Marcin
Abstract : Supplemental digital content is available in the text.